Minimum wiping pressure and number of wipes that can remove dirt during bed baths using disposable towels: a multi-study approach - Issei Konya; Kotone Nishiya; Inaho Shishido; Marie Hino; Kazuhiro Watanabe; Rika Yano (BMC, 2023)
Abstract Background Friction irritation by wiping increases the risk of skin problems. In bed baths with cotton towels, wiping three times with weak pressure (10-20 mmHg ≈ 1333-2666 Pa) can remove dirt while maintaining skin barrier function. However, few studies have examined the appropriate frictional irritation with disposable towels. This study aimed to analyse the wiping pressure and number of wipes currently applied by nurses when using disposable towels during bed baths and propose the minimum values for removing dirt from the skin. Methods This multi-study approach consisted of cross-sectional and crossover design components. In Study 1, 101 nurses in two hospitals were observed by recording the wiping pressure and number of wipes when using both disposable (nonwoven) and cotton (woven) towels. Wiping pressure and number of wipes by towel materials were analysed using a linear mixed model. In Study 2, 50 adults received oily and aqueous dirt on their forearms, which were wiped six-times with disposable towels, applying randomly assigned pressure categories. We used colour image analysis and a linear mixed model to estimate the dirt removal rate for each combination of wiping pressure and number of wipes. Results Study 1 showed that although wiping pressure did not differ by towel material, the number of wipes was significantly higher for disposable wipes than cotton wipes. Approximately 5% of nurses applied strong wiping pressure or wiped too often. In Study 2, wiping three times with disposable towels at least 5-10 mmHg achieved dirt removal rates of ≥80%. Conclusions Some nurses excessively wiped using disposable towels, which might cause skin problems. However, excessive wiping is not required to adequately remove dirt, regardless of the towel material used in various clinical situations. We recommend wiping at 10-20 mmHg of pressure (just like stroking gently) at least three times to improve the quality of bed baths. These findings highlight the need to develop skin-friendly bed bath educational programmes, particularly using appropriate frictional irritation to reduce the risk of skin problems.